2015
DOI: 10.1002/stem.1876
|View full text |Cite
|
Sign up to set email alerts
|

Pwp1 Is Required for the Differentiation Potential of Mouse Embryonic Stem Cells Through Regulating Stat3 Signaling

Abstract: Leukemia inhibitory factor/Stat3 signaling is critical for maintaining the self-renewal and differentiation potential of mouse embryonic stem cells (mESCs). However, the upstream effectors of this pathway have not been clearly defined. Here, we show that periodic tryptophan protein 1 (Pwp1), a WD-40 repeat-containing protein associated with histone H4 modification, is required for the exit of mESCs from the pluripotent state into all lineages. Knockdown (KD) of Pwp1 does not affect mESC proliferation, self-ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…PRC2 binds and methylates histone H3K27 within nucleosomes (Margueron and Reinberg, 2011; Simon and Kingston, 2009), consistent with the co-localization of its Suz12, Ezh2, and Mtf2 subunits (Zhang et al, 2011) with nucleosome footprints. Similarly, Pwp1 (a WD40-repeat containing protein) occupies regions marked with H4K20me3 and regulates H4K20 methylation at some sites (Shen et al, 2015) and Ring1b (an E3 ubiquitin ligase) monoubiquitinates H2AK119 (Wang et al, 2004). Furthermore, Lsd1 is a histone H3 lysine demethylase (Shi et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…PRC2 binds and methylates histone H3K27 within nucleosomes (Margueron and Reinberg, 2011; Simon and Kingston, 2009), consistent with the co-localization of its Suz12, Ezh2, and Mtf2 subunits (Zhang et al, 2011) with nucleosome footprints. Similarly, Pwp1 (a WD40-repeat containing protein) occupies regions marked with H4K20me3 and regulates H4K20 methylation at some sites (Shen et al, 2015) and Ring1b (an E3 ubiquitin ligase) monoubiquitinates H2AK119 (Wang et al, 2004). Furthermore, Lsd1 is a histone H3 lysine demethylase (Shi et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in mouse, Drosophila, and budding yeast (Saccharomyces cerevisiae) have shown that PWP1 associates with the chromatin and has a putative role in gene regulation (Casper et al, 2011;Suka et al, 2006). In Drosophila polytene chromosomes, PWP1 localization overlaps with that of active Pol II (Casper et al, 2011), and in mouse embryonic stem cells (mESCs), PWP1 association with chromatin correlates with high levels of H4K20me3 modification (Shen et al, 2015). PWP1 has recently been implicated in stem cell function.…”
Section: Introductionmentioning
confidence: 99%
“…PWP1 has recently been implicated in stem cell function. Loss of PWP1 function impairs the differentiation potential of mESCs (Shen et al, 2015), and Drosophila mutants lacking PWP1 display impaired male germline stem cell maintenance, leading to sterility (Casper et al, 2011). Therefore, the fly gene was named no child left behind.…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic stem cells (ESCs) can self‐renew and differentiate into three germ layers and are a valuable tool in regenerative medicine and developmental biology. The ESC differentiation process is precisely regulated by various factors, including signaling pathways and epigenetic events . Once the regulatory balance is disrupted at the initiation stage of differentiation, ESCs will not be induced to differentiate into the correct lineage.…”
Section: Introductionmentioning
confidence: 99%
“…The ESC differentiation process is precisely regulated by various factors, including signaling pathways and epigenetic events. 1,2 Once the regulatory balance is disrupted at the initiation stage of differentiation, ESCs will not be induced to differentiate into the correct lineage. However, the exact regulatory mechanism underlying the initiation of ESC differentiation remains unclear.…”
Section: Introductionmentioning
confidence: 99%